Science in propaganda and popular culture in the USSR under Khruschëv (1953-1964) - Froggatt, M (2006)
﻿ This thesis is the first detailed study of the way in which science and technology were portrayed in propaganda and popular culture during the Khrushchëv period, a time when the Soviet leadership invested significant resources, both at home and abroad, in order to capitalise on its scientific achievements. It draws upon a wide range of previously unseen materials from the archives of the RSFSR Ministry of Education, the Soviet Academy of Sciences, the State Committee on Radio and Television and the Central Committee of the CPSU. It provides the first archive-based analysis of the lecturing organisation 'Znanie', which was crucial to the dissemination of Soviet propaganda in the post-war period. The thesis also makes use of a variety of published sources, such as popular science publications and journals, as well as a number of Soviet films from the Khrushchëv period. The thesis examines the manner in which scientific information was disseminated to the Soviet public and the ways in which public scientific opinion was able to participate in, and influence, this process. It is shown that a general lack of institutionalised control enabled members of the scientific intelligentsia to exercise a degree of control over the content of scientific propaganda, often in a very idiosyncratic fashion. The way in which the rhetorical and ideological presentation of science changed during the Khrushchëv period (often identified as 'the Thaw') is analysed, and it is shown that while Soviet popular science did become increasingly open to foreign influence it became preoccupied with new threats, such as generational and personal conflict. The thesis also uses the available sources to consider popular responses to scientific propaganda and, in particular, whether attempts to use scientific-atheistic propaganda to create a 'materialist' worldview amongst Soviet citizens met with any success. The thesis provides detailed case studies of the use of science in Khrushchëv's atheistic campaigns, of propaganda surrounding early Soviet achievements in the space race and of the portrayal of the Lysenko controversy in the popular media.